(untitled) (Journal of Scientific Research, 2024)
In the present work, monomers acrylamide (AAm) and vinyl imidazole (VI) were co-polymerized in the presence of carboxymethyl cellulose (CMC) to yield a totally un-crosslinked solid hydrogel electrolyte (SHE) with fair self-healing property. The SHE was characterized by FTIR, XRD, SEM, and TGA analysis. The surface texture, as revealed by SEM analysis, was observed to be fairly smooth. The hydrogel electrolyte exhibited pH-dependent swelling behavior with percent equilibrium swelling (PES) of 5170, 1892, and 5163 in the swelling media of pH 1.0, 6.8, and 13.0, respectively. In addition, the kinetic swelling was best interpreted by the Power function model, revealing a chain relaxation-controlled water uptake at pH 1.0 and 13.0. The SHE showed an excellent self-healing property, which was confirmed by the “LED glowing” experiment. As compared to its original elongation of 200 %, the self-healed hydrogel exhibited an elongation of 157 %, thus showing a fair restoration tendency.